MODELING OF ADS-B MESSAGES TRANSMISSION VIA SATELLITE USING MIMO SYSTEMS - Kharchenko, Volodymyr; Bo, Wang; Grekhov, Andrii; Kostynska, Julia (Proceedings of National Aviation University (archive), 2014)
The original model of aeronautical satellite MIMO communication channel “Aircraft–to–Satellite–to– Ground Station” was created using MATLAB Simulink software. MIMO 2×1 and 3×2 fading uplink/downlink channels with antenna diversity were analyzed. Results were compared with AWGN uplink/downlink channels. On the base of these models channels integrity was investigated and dependences of Bit Error Rate on the ratio Eb/N0 were received.